STUDI KASUS PERHITUNGAN TEGANGAN PADA FLAT BELT DALAM APLIKASI MESIN IHR: STUDI KASUS PERHITUNGAN TEGANGAN PADA FLAT BELT DALAM APLIKASI MESIN IHR - Muhammad, Rouf; Safi'i, Muhamad; Ramdhani, Ahmad; Fahmi, Muhammad Idrokul (STORAGE: Jurnal Ilmiah Teknik dan Ilmu Komputer, 2024)
The Continuously Variable Transmission (CVT) automatic transmission system is a power transmission component widely used in various industrial sectors such as manufacturing, paper, automotive, and electric power. The decision to use this transmission is made due to its ease of maintenance, affordability, and its ability to operate within various power and speed ranges. Key components of the CVT automatic transmission system include flat belts, pulleys, rollers, CVT springs, CVT clutch linings, and clutch clutches. Calculation analysis will be conducted to determine the maximum stress of the flat belt, identify the material of the flat belt, and calculate the lifespan of the flat belt using the IHR machine. The results of the calculation show that the tight side stress is 383.3639 N, the loose side stress is 64.867 N, and the belt material stress is 3.1 N/mm2. These optimal stress and material stress values are deemed suitable for use.